Ḥūma. Musica rap e convergenza linguistica in arabo tunisino - Tarquini, Maura (Folia Orientalia, 2026)
On January 14, 2011, Zayn al-‘Ābidīn Bin ‘Alī resigned, left Tunisia and took refuge in Saudi Arabia following the revolts born in Sīdi Būzīd after the suicide of Bū-‘Azīzī. The Arab Spring in Tunisia was not a popular uprising perpetrated by the lower class and the unemployed young people: the committees of the lawyers and the magistrates who joined the protests, proved the active participation of the middle class. However, the Revolution did not alleviate the popular unrest, and it did not reduce the social imbalances. The diastratic varieties, already existing before the Revolution, are the linguistic reflection of the social situation. After 2011 the main actors of the protests, proceeding from the lowest and youngest class, came back to the Ḥūma, the ghetto, in which anger and frustration flourish. The description of the life in the Ḥūma, has become the main topic of many songs written by the new generation of Tunisian artists who sing in the slang of the lower class. Despite they proceed from the upper class, they have become the spokesmen of the malaise that hovers in the poor neighborhoods. Guerrero (2012) analysed linguistically Rāyǝs lǝ-Blād, a song by the Tunisian rapper El Général, appeared on internet on February 8th, 2011, few days before the escape of Bǝn ԑAlī. Rāyǝs lǝ-Blād is an example of the artistic denunciation of the political oppression and the social degradation. The songs of artists such as Kafon, Hamzaoui Med Amin and Balti, which appeared after the Revolution instead, are not acts of protest, they just represent the ordinary life of the ūlād ǝl-Ḥūma in the ghetto. What linguistic dynamics are put in place by these singers? After a historical-etymological reconstruction related to the word Ḥūma, it will be shown how this group of artists practiced, on the one hand, the divergence with respect to the prestigious variety of the capital, on the other, the convergence towards the language of the Tunisian poorest class.